Vulnerability Assessment of Hazmat Storage Tanks to Shooting Attacks - Matteo Iaiani; Alessandro Tugnoli; Valerio Cozzani (Chemical Engineering Transactions)
There is historical evidence of chemical and process facilities being the target of shooting attacks. A fundamental step in security risk assessment is the analysis of the vulnerability of the target installation against the physical effects of the attacks. While in the open literature, the vulnerability of industrial facilities to attacks with improvised explosive devices and to incendiary attacks have been assessed, the development of adequate damage models for the assessment of the vulnerability of process and HAZMAT storage equipment against shooting attacks is still lacking. The present study addresses this gap and provide a novel scientifically based modelling approach to calculate baseline values of standoff distances for atmospheric storage equipment that can be used to assess the potential damage of shooting attacks targeting them. The calculations were done for a standardized set of projectiles using perforation models suitable for industrial installations and selected in a previous work. The results show that the range of standoff distances varies depending on the type of firearm used. Standoff distances resulted in the range of less than 10 meters in case of handgun projectiles and up to 1130 meters in case of hard-core rifle projectiles. Important differences in standoff distances were found for atmospheric tanks.